2003
DOI: 10.1053/jlts.2003.50174
|View full text |Cite
|
Sign up to set email alerts
|

Death from donor-transmitted malignancy despite emergency liver retransplantation

Abstract: Transplantation of organs procured from donors with malignancies identified subsequent to implantation presents a significant dilemma regarding the optimal management strategy to simultaneously minimize the risk for cancer transmission and recipient morbidity. In this report, we present a patient who underwent orthotopic liver transplantation for hepatitis B cirrhosis. The donor had no previous history of cancer. On autopsy, enlarged mediastinal lymph nodes led to the discovery of a 1-cm lung tumor. Histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 11 publications
(12 reference statements)
0
31
0
Order By: Relevance
“…Lipshutz et al (14) reported the case of a liver recipient who was urgently retransplanted after the donor was found to harbor a pulmonary adenocarcinoma with metastatic mediastinal disease. This patient nevertheless succumbed to this donor transmitted malignancy 11 months after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Lipshutz et al (14) reported the case of a liver recipient who was urgently retransplanted after the donor was found to harbor a pulmonary adenocarcinoma with metastatic mediastinal disease. This patient nevertheless succumbed to this donor transmitted malignancy 11 months after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Again, in a case of re-transplantation of a liver allograft recipient with localized adenocarcinoma from the donor, the recipient was doing well at the one year follow up (Donovan et al 1997). In contrast, despite emergency re-transplantation in a liver recipient from a donor found to have metastatic adenocarcinoma in the lung, the recipient died within 7 days due to metastatic adenocarcinoma (Lipshutz et al 2003).…”
Section: Solid Organ Transplantsmentioning
confidence: 97%
“…Besides these retrospective studies there have been many case reports of tumor transmission (melanoma, sarcoma, renal cell carcinoma, etc) (Stephens et al 2000;Milton et al 2006;Neipp et al 2006;Cankovic et al 2006;Detry et al 2005;Morris-Stiff et al 2004;Gerstenkorn and Thomusch 2003;Lipshutz et al 2003;Loren et al 2003;Kakar et al 2002;Barrou et al 2001;Winter et al 2001;Conlon and Smith 1995;Oesterwitz and Lucius 1991;Barnes and Fox 1976), some of which may have been included in the reviews described.…”
Section: Non-cns Tumor-transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organ transplant surgeons have established a registry of transplants from organ donors with a history of cancer (92,93). The cancers at highest risk of being transmitted to recipients include central nervous system tumors, choriocarcinoma, breast cancer, renal carcinoma, and lung cancers (94)(95)(96)(97)(98)(99)(100). The overall risk of death from a donor-derived malignancy is well less than 1% (101,102).…”
Section: Risk Of Malignancy From Ovarian Cortical Tissue Autotransplamentioning
confidence: 99%